Correlation between facial growth patterns and cortical bone thickness assessed with cone-beam computed tomography in young adult untreated patients - Francesca Gaffuri; Gianguido Cossellu; Cinzia Maspero; Valentina Lanteri; Alessandro Ugolini; Giulio Rasperini; Iury O. Castro; Marco Farronato (Elsevier, 2021)
Background: The vertical facial growth pattern is one of the most important issue in the orthodontic diagnosis and treatment. Previous studies investigated the association between interdental bone thickness and facial divergence using mainly bidimensional analysis. When two-dimensional dental radiographic views are not sufficient for diagnosis and measurements, cone-beam computed tomography (CBCT) images should be used to assess the alveolar bone structure three-dimensionally and with high accuracy and reliability.The aim of the present study was to evaluate the correlation between alveolar bone thickness and facial divergence in young adults untreated patients using a three-dimensional method analysis with CBCT images. Methods: Records of 30 untreated patients (mean age 16 ± 2 years) with Angle Class I and mild to moderate crowding were analyzed. Subjects were classified as hypodivergent (<39˚), normodivergent (41 ± 2˚), and hyperdivergent (>43°). according to the inter-maxillary angle between the sagittal maxillary plane (ANS-PNS) and the mandibular plane (GN-ME). The alveolar bone thickness measurements were taken for the buccal and palatal/lingual surfaces of maxillary and mandibular anterior teeth. Axial-guided navigation (AGN) was used to locate all landmarks using a specific software (Horos 3.0). Results: The statistical analysis showed a significant difference between the hypodivergent and hyperdivergent group regarding buccal bone height (P = 0.005), buccal apical bone thickness (P = 0.003) and palatal mid-root bone thickness (P = 0.006). Moreover, buccal bone height (P = 0.006) was found to be statistically significant different in normodivergent compared with hypodivergent individuals. Conclusions: Facial types were found to be correlated with alveolar bone thickness. The hyperdivergent subjects presented thinner alveolus bone in the anterior maxilla and at almost all sites in the mandible. Clinicians should be aware of the possibility of thin cortical bone plates in hyperdivergent patients, reducing antero-posterior movements to avoid fenestration and dehiscence.